Lack of Antibodies to Clotting Factors in the Blood of Hemophiliacs Refractory to Transfusions) - Penalver, Jorge A; Holburn, R. R; Carroll, R. T; Tocantins, L. M (Thrombosis and Haemostasis, 1957)
1. The blood of 11 Hemophilia “A” patients refractory to transfusions has been studied for the presence of precipitins against certain clot-accelerating fractions. The tests were invariably negative. Identical results were observed in 10 Hemophilia “A” patients non-refractory to transfusions, in 2 cases of Hemophilia B, in 5 patients with miscellaneous conditions and in 11 normal individuals.2. When unheated Fraction I of Cohn is used as antigen, false positive results due to formation of fibrin clots were observed with all human sera tested. This may be a source of error in the interpretation of the tests, especially in the blood of refractory Hemophilia “A” patients with an unusually long clotting time and slow prothrombin conversion.3. These observations do not support the hypothesis that the refractory state to blood transfusions observed in some Hemophilia “A” patients is due to the presence of antibodies against certain clot-accelerating fractions of normal plasma.